Sites of Modernity Asian Cities in the Transitory Moments of Trade, Colonialism, and Nationalism - Wongsurawat, Wasana; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelber(Imprint), 2016)
This book investigates, compares and contrasts the experience of entering into and engaging in modernity and the modern era in many parts of the Asian continent. It focuses on the coming into being, development, and transformation of major urban centers from Tokyo to Mumbai from the late 19th century to the present, providing a broad overview of this crucial period of transition in Asia, not only from diverse geographical and historical perspectives, but also incorporating a broad range of further disciplines.
Introduction -- Chapter 1 Teaching Civilization:The Role of a French Education in the Development of Modernity in Shanghai -- Chapter 2 Scientific Institutions as Sites for Dissemination and Contestation: Emergence of Colonial Calcutta as a Science City -- Chapter 3 Management of 'Public Spaces': Case-Study of Roads in Bangkok in the Reign of King Rama V -- Chapter 4 A city-state as migrant nation: Singapore from the colonial to the Asian modern -- Chapter 5 Whose Home? Cultural-pluralism and Preservation of Japanese Colonial Heritage in Taipei City -- Chapter 6 Home-Base of an Exiled People: Hong Kong and Overseas Chinese Activism from Thailand -- Chapter 7 Bangkok: From an Antique to a Modern City -- Chapter 8 Nationalism in Indian Architecture: A Modern Trajectory in Twentieth Century India -- Chapter 9 From the Demolition of Monasteries to the Installation of Neon Lights: The Politics of Urban Construction in the Mongolian People's Republic. .
Keywords: History; Anthropology; Migration